The effect of mindfulness-based stress reduction on presenteeism among ICU nurses: A cluster randomized controlled trial - Xiaoli Liu; Shu Luo; Xianxiu Wen; Xiahong Huang; Jijun Wu; Min Chen; Ping Jia (PLoS ONE, 2025)
Background Due to high-pressure environments, heavy workloads, and working in “three-shift” schedules, Intensive Care Unit (ICU) nurses experience high-level presenteeism. This may compromise nursing quality and patient safety and damage nurses’ physical and mental health. Therefore, there’s an urgent need for effective interventions to promote the healthy development of nursing human resources and maintain nursing team stability. Aim To evaluate the effect of an 8-week Mindfulness-Based Stress Reduction (MBSR) training on presenteeism among ICU nurses. Methods ICU nurses with high levels of presenteeism were invited to participate in the study. The ICU wards were randomly assigned to either the intervention group or the control group. The intervention group (40 nurses) received an 8-week MBSR program delivered by a certified mindfulness therapist. In comparison, the control group (40 nurses) received standard psychological counseling, including emotional control, psychological regulation, and sleep management. Both groups were assessed using the Stanford Presenteeism Scale-6 (SPS-6) and the Five Facet Mindfulness Questionnaire (FFMQ) before and after the intervention, and 12 weeks after the intervention. Methods This study employed a cluster randomized controlled trial with a two-arm design. ICU nurses with high presenteeism were invited and randomly assigned to groups by floor. The intervention group (40 nurses) underwent an 8-week MBSR program delivered by a certified mindfulness therapist, while the control group (40 nurses) received standard psychological counseling, including emotion regulation, psychological adjustment, and sleep management. Both groups were assessed using the Stanford Presenteeism Scale-6 (SPS-6) and the Five Facet Mindfulness Questionnaire (FFMQ) at baseline, post-intervention, and 12 weeks post-intervention. Results Linear mixed model analysis showed significant group, time, and group-time interaction effects on SPS-6 scores ( P < 0.05). The experimental group had significantly lower SPS-6 scores at 8 and 12 weeks post-intervention than the control group and their pre-intervention scores ( P < 0.05). For FFMQ scores, significant group and time effects ( P < 0.05) but no significant group-time interaction ( P > 0.05) were found. The experimental group’s FFMQ scores were significantly higher at 8 and 12 weeks post – intervention than the control group and their pre-intervention scores ( P < 0.05). Conclusion The Mindfulness-Based Stress Reduction intervention was associated with increased mindfulness levels over time, and it significantly reduced presenteeism, with sustained effects observed over time. Clinical implications for nursing management MBSR, as a psychological intervention method, has the advantages of improving nurses’ mental health and work efficiency, reducing presenteeism, and ensuring patient safety. Nursing managers can integrate MBSR into hospital policies by organizing regular MBSR sessions on mental health days or during team-building activities. This not only enhances nurses’ psychological resilience but also promotes a positive work environment, contributing to a safer and more efficient healthcare setting. Patient or Public Contribution Participants were involved solely in the data collection process. No participant contributions were required for the study’s design, outcome measurement or implementation.